Pengembangan Waterfront City Kawasan Pasar Kota Kuala Tungkal - Syahruji Syahruji; Nengah Tela; Jonny Wongso (Jurnal Talenta Sipil, 2023)
The development of activities and the potential of the Kuala Tungkal City Market Area which has visual and physical contact oriented towards the waters is the basic issue of the starting point in making plans with an area development approach with a waterfront concept. Activities developed in the waterfront area are inseparable from the potentials of the area. This potential will also influence the motivation for the development of the waterfront concept which generates ideas in the utilization of spatial functions. The aim of the development is for the waterfront area and other functions as well as a good and clear grouping of areas according to their functions. This study uses a rationalistic approach in formulating the waterfront concept approach in the development of the Kuala Tungkal City Market area.